Analisis Perilaku eWOM Opini Vaksinasi dengan Pendekatan Theory of Planned Behavior - Pamungkas, Benni Ahdiyana; Nursal, Adman (UI Scholars Hub, 2021)
Ajzen’s theory of planned behavior (TPB) has been proven in many fields to predict human be- havior. Discussion of eWOM behavior based on the theoretical approach, to the author’s knowledge, has not been widely found. This study aims to examine six hypotheses to analyze eWOM behavior by TPB approach. This research methode is survey. Sampling uses a non-probability method with judgmental techniques. The unit sample is 165 respondents who already know or post a vaccination opinion twibbon on Facebook. The questionnaire is the measurement instrument in this research. The study reveals that three hypotheses were rejected and the other three were not rejected. The behavior of eWOM opinion on vaccination is proven to be infuenced by behavior intentions. Intentions are in- fluenced by attitudes and injunctive norms toward behavior eWOM behavior on vaccination opinion. The theoritical implication of the research is to strengthen the intial theory of TPB and other previous findings. The managerial implication of this research is result of research identify several key vari- abels that influence the eWOM behavior of vaccination opinion and its main target audience.